Evaluating the physical stability of integrated tailings deposit San Andrés (Peru) - Paulino José Avellaneda-Puri; Carmen Judith Avellaneda-Cristóbal (Minería y Geología, 2020)
Tailings deposit of San Andrés Benefit Concession, located in La Libertad, Peru, stores tailings in two integrated deposits, one for flotation tailings and the other for cyanidation tailings; the storage is done by the central axis method. The purpose of this study was to determine the physical stability during the operation phase, aimed at controlling the quality and quantity of tailings; the height and slope angles of the main dike; to keep water mirror away from the dike; to conserve the difference between the crown of the dike and the level of the water mirror over a minimum height of 2 m (free edge); and detecting deformations or settlements, abnormal leaks in the dike or cracks presence. Results of the safety factors for both tailings deposits, showed higher values than the minimum safety factors required by current legislation, so it is concluded that both structures are physically stable, both in static and pseudo-static conditions.